The Impact of Family Income on Body Mass Index and Self-Rated Health of Illiterate and Non-illiterate Rural Elderly in China: Evidence From a Fixed Effect Approach - Xin, Yu; Ren, Xiaohui (Frontiers in Public Health, 2021)
Background: Rural communities worldwide are experiencing the most significant levels of aging. And family income plays an indispensable role in the life support of the rural elderly. This study aimed to investigate whether the association between annual family income per capita and body mass index and self-rated health of rural elderly is moderated by education during fast economic development. Methods: We chose the fixed-effects model to analyze the impact of the annual family income per capita change on body mass index (BMI) and self-rated health (SRH) based on a large, nationally representative longitudinal dataset of rural respondents aged above 60 from three waves of the China Family Panel Studies (CFPS) from 2010 to 2018. Results: We found that family per capita income only positively affects the SRH of the rural illiterate elderly. It is also positively correlated with BMI, especially for the illiterate elderly, which may be a causal relationship. Conclusion: These results contribute to developing more targeted strategies in the context of a developing country. And it also reminds us to consider the educational differences in rural areas when investigating causal relationships.